Development of PBL-based digital flipbook on human excretory system for SMA/MA students - Syakira Amalia Hasibuan; Rahmadina Rahmadina (Himpunan Pengembang Kurikulum Indonesia, 2025)
The rapid advancement of technology demands innovation in developing interactive and effective learning media. This study aims to develop digital flipbook learning media based on Problem-Based Learning (PBL) for teaching the human excretory system, to improve students’ conceptual understanding and learning outcomes. The development process employed the 4D model, which includes the stages of defining, designing, developing, and disseminating. The flipbook was validated by material and media experts and further tested by teachers and students to evaluate its feasibility, practicality, and effectiveness. The findings indicate that the PBL-based digital flipbook is valid, practical, and effective in supporting students’ comprehension through interactive presentations, visual illustrations, and the integration of contextual problems. Furthermore, the flipbook enhances student motivation and engagement throughout the learning process. Therefore, this digital flipbook serves as an innovative alternative learning medium to support biology education, particularly for abstract topics such as the excretory system, and can also function as an accessible self-learning resource at any time and from anywhere. Abstrak Perkembangan teknologi menuntut adanya inovasi dalam penyediaan media pembelajaran yang interaktif dan efektif. Keberagaman metode pembelajaran membuat guru dapat melakukan pengembangan media pembelajaran yang cocok untuk kegiatan belajar di kelas. Penelitian ini bertujuan mengembangkan media pembelajaran flipbook berbasis Problem Based Learning (PBL) pada materi sistem ekskresi manusia untuk meningkatkan pemahaman konsep dan hasil belajar peserta didik. Proses pengembangan dilakukan menggunakan model 4D yang mencakup tahap pendefinisian, perancangan, pengembangan, dan penyebaran. Media divalidasi oleh ahli materi dan ahli media, kemudian diuji pada guru serta peserta didik untuk menilai aspek kelayakan, kepraktisan, dan efektivitasnya. Hasil penelitian menunjukkan bahwa flipbook berbasis PBL dinyatakan valid, praktis, dan efektif dalam membantu peserta didik memahami materi melalui penyajian interaktif, ilustrasi visual, serta integrasi permasalahan kontekstual. Flipbook ini juga meningkatkan motivasi belajar dan keterlibatan peserta didik selama proses pembelajaran. Dengan demikian, media pembelajaran flipbook berbasis PBL dapat dijadikan alternatif inovatif untuk mendukung pembelajaran biologi, terutama pada materi yang bersifat abstrak seperti sistem ekskresi, sekaligus menjadi sumber belajar mandiri yang mudah diakses kapan saja dan di mana saja. Kata Kunci: flipbook; media pembelajaran; pembelajaran berbasis masalah; sistem ekskresi